Chemical Changes Under Heat Stress and Identification of Dendrillolactone, a New Diterpene Derivative with a Rare Rearranged Spongiane Skeleton from the Antarctic Marine Sponge Dendrilla antarctica - Andrea Prófumo; Conxita Avila; Adele Cutignano (Marine Drugs)
The waters around the western Antarctic Peninsula are experiencing fast warming due to global change, being among the most affected regions on the planet. This polar area is home to a large and rich community of benthic marine invertebrates, such as sponges, tunicates, corals, and many other animals. Among the sponges, the bright yellow Dendrilla antarctica is commonly known for using secondary diterpenoids as a defensive mechanism against local potential predators. From the dichloromethane extract of sponge samples from Deception Island collected in January 2023, we isolated a novel derivative with an unusual β-lactone diterpene skeleton here named dendrillolactone (1), along with seven previously described diterpenes, including deceptionin (2), a gracilane norditerpene (3), cadlinolide C (4), a glaciolane norditerpene (5), membranolide (6), aplysulphurin (7), and tetrahydroaplysulphurine-1 (8). Here, we also report our studies on the changes in the chemical arsenal of this sponge by slow temperature increase in aquaria experiments. Despite being a species capable of inhabiting volcanically active areas, with frequent water temperature fluctuations due to the existing fumaroles, the results show that diterpenes such as deceptionin, cadlinolide C, membranolide, and tetrahydroaplysulphurin-1 seem to be susceptible to the temperature increase, resulting in a trend to higher concentrations. However, temperatures above 4 °C severely affected sponge metabolism, causing its death much earlier than expected. Further research on the roles of these natural products in D. antarctica and their relationship to the sponge’s resilience to environmental changes should help to better understand the defensive mechanisms of Antarctic marine benthos in the context of global change.